The importance of imitation, network position, and international experience for biotechnology SMEs growth in Johor biotechnology and biodiversity corporation - Murrali Manugaran, 1992-, author; Mohd. Effandi Yusoff, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018